Research Progress of Nuclear Energy Batteries for Ocean Observation Equipment - Rongyu SHAO; Yushu YANG; Xu WANG; Jianxiong SHAO; Aixiang YANG (Journal of Isotopes)
For the ocean observation equipment，nuclear power supply has irreplaceable advantages. In recent years，due to the urgent need to develop all-round and multi-dimensional ocean observation and exploration equipment in China，the radioactive thermoelectric generatorapplied in the ocean can be successfully applied to the energy supply of underwater observation and exploration equipment，and is in the stage of research and exploration in China. In this paper，the Marine radioisotope thermoelectric generator is summarized，and the structure of radioisotope thermoelectric generator used in Marine observation equipment in the United States and Russia is analyzed according to the relevant published research. The advantages and disadvantages of their structural factors are compared，and the material environment of different structural designs is different，which has important reference value for the future design of radioisotope thermoelectric generator.